(3EOGQI GdeHjYGJ (B:s (3eONd cej hSdhcj hGOGQj (B/s - (3GdYScQj, CMeO TGcQs ((3YeGf(B: s (3OGQ RgQGf(B, s, 2008)
(3OQGSI GdShb(B- (3eGgjI hXjaI GdeHjYGJ(B- (3EOGQI Gdbhi GdHjYjI(B- (3WQjb Jbjje COGA efOhHj GdHjY(B- (3GdCSGdjH GdcejI aj GdeSJNOeI aj JNWjW GdeHjYGJ(B- (3CSGdjH GdJfHD HGdeHjYGJ(B- (3GdQbGHI hGdJbjje GdHjYjs
(3cTGa GdeUWdMGJ U(B.203 (3GdeQGLY U(B.245s
Keywords: (3EOGQI GdEfJGLs; (3COGQI GdeHjYGJs; (3GdShbs